2002
DOI: 10.1159/000063648
|View full text |Cite
|
Sign up to set email alerts
|

Psychological, Allergic, and Toxicological Aspects of Patients with Amalgam-Related Complaints

Abstract: Background: To deepen the understanding of the numerous unspecific complaints which are related to the dental material amalgam both in patients and physicians, an interdisciplinary case-control study regarding toxicological, allergic, psychological and psychiatric aspects was conducted. Forty patients with amalgam-associated complaints were compared to a well-matched group of 40 amalgam bearers without complaints. Methods: Patients and controls underwent a dental examination, which included recording of the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 21 publications
(26 reference statements)
0
11
1
1
Order By: Relevance
“…On the other hand, several other factors may influence patients' experience of health. It is well established that the differences could be associated with psychological factors (23)(24)(25)(26), One study indicated that a majority of patients with health complaints related to dental amalgam frequently had mental disorders, including anxiety, depression, and somatization (27), However, this does not explain the fact that the majority ofthe patients in the present study reported that they felt better after having their amalgam restorations replaced. Interestingly, it has been reported that health improvement after removal of amalgam restorations was related to mercury excretion in urine prior to removal (13), It has also been suggested that the improvement may be due to a normal fluctuation over time among patients with severe symptoms (22), Most of the patients recommended to have dental materials replaced actually did so.…”
Section: Discussioncontrasting
confidence: 57%
“…On the other hand, several other factors may influence patients' experience of health. It is well established that the differences could be associated with psychological factors (23)(24)(25)(26), One study indicated that a majority of patients with health complaints related to dental amalgam frequently had mental disorders, including anxiety, depression, and somatization (27), However, this does not explain the fact that the majority ofthe patients in the present study reported that they felt better after having their amalgam restorations replaced. Interestingly, it has been reported that health improvement after removal of amalgam restorations was related to mercury excretion in urine prior to removal (13), It has also been suggested that the improvement may be due to a normal fluctuation over time among patients with severe symptoms (22), Most of the patients recommended to have dental materials replaced actually did so.…”
Section: Discussioncontrasting
confidence: 57%
“…Thus, our data definitely support the necessity to be aware of and offer help for the psychological dimension of amalgam intolerance. We found statistically significant correlations between symptom scores and three different objective measures of mercury level in the range from r = 0.25 to 0.39 with regard to baseline values. Corresponding correlation coefficients in the literature are usually lower or not statistically significant compared with the zero correlation (10, 24). The number of amalgam fillings (often used in the literature to estimate mercury burden) is probably a less precise measure and also usually fails to be associated with symptom scores (11, 20, 22, 31) – this was also the case in the study presented here ( r = 0.13).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies involved personality inventories to analyze relations between personality factors and subjective amalgam intolerancewith inconsistent findings. While some found indications of specific personality traits in amalgam patients (18)(19)(20)(21) others failed to show any relationship or differences compared with controls (22)(23)(24).…”
mentioning
confidence: 99%
“…Gottwald et al (20) found that persons with amalgam complaints use a more vigilant coping style when faced with environmental threats by actively seeking out threatening information to reduce the uncertainty. This coping style has been suggested to lead to a rather ruminative focus on the potential negative health effects of amalgam (20). The specific cognitive style has been considered similar to that of psychosomatic patients (10,22,31,32).…”
Section: Discussionmentioning
confidence: 99%